THE PLAYFULNESS: "RESIGNIFYING THE TEACHING AND LEARNING PRACTICES OF TEACHERS IN THE CLASSROOM IN ENGLISH LANGUAGE SKILLS’ - Rocha Alfonseca, Márcia; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
This article aims to understand the role of playfulness in the Elementary School classroom - Final Years, in Bom Jesus da Lapa - Bahia, in the public educational context and has as a way of collaborating for the student’s development in the teaching and learning process. learning language skills in English, as well as offering teachers pedagogical training on the use of games and recreational activities as a tool that facilitates creativity and interest in building knowledge of a new language. Based on a bibliographic research, we used the following authors as theoretical frameworks: Kishimoto (2011), Nicholls (2001), Feijó (1992), Santos (2006). The methodology used was action research developed at Escola Municipalizada Edivaldo Boaventura. Data were collected through semi-structured questionnaires with applied questions, and interpreted, in the light of systematized theoretical approaches. The research results showed a favorable acceptance of the playful methodology in the final years, due to the consensus that was presented through the games, where the student not only has fun, but also fully develops their potential.